Proposition of decision limits for serum lipids in Brazilian children aged one to 13 years - Natasha Slhessarenko; Cor J.F. Fontes; Maria Eduarda Slhessarenko; Raymundo S. Azevedo; Adagmar Andriolo (Brazilian Society of Pediatrics, 2019)
Objective: To determine decision limits for total cholesterol, LDL‐cholesterol, non‐HDL cholesterol, HDL‐cholesterol, and triglycerides in healthy children and adolescents from Cuiabá, Brazil. Methods: This was a cross‐sectional study of 1866 healthy children and adolescents randomly selected from daycare centers and public schools in Cuiabá. The desirable levels of serum lipids were defined using the classic criteria, i.e., total cholesterol, LDL‐cholesterol, non‐HDL cholesterol, and triglycerides levels below the P75 percentile, and HDL‐c above the P10 percentile. Results: For CT, P75 was: 160 mg/dL for the age range of 1 to <3 years, 170 mg/dL for ≥3 to <9 years, and 176 mg/dL for ≥9 to <13 years. For non‐HDL cholesterol, it was 122 mg/dL for the age range of 1 to <13 years. For LDL‐c, it was 104 mg/dL at the age range of 1 to <9 years and 106 mg/dL from ≥9 to <13 years. For TG, it was 127 mg/dL from 1 to <2 years; 98 mg/dL from ≥2 to <6 years; and 92 mg/dL from ≥6 to <13 years. As for HDL‐cholesterol, P10 was 24 mg/dL, 28 mg/dL, 32 mg/dL, and 36 mg/dL, for the age ranges of 1 to <2 years, ≥2 to <3 years, ≥3 to <4 years, and ≥4 to <13 years, respectively. Conclusion: The decision limits for the serum lipid levels defined in this study differed from those observed in the current Brazilian and North‐American guidelines, especially because it differentiates between the age ranges. Using these decision limits in clinical practice will certainly contribute to improve the diagnostic accuracy for dyslipidemia in this population group. Resumo: Objetivo: Determinar limites de decisão (LD) para o colesterol total (CT), LDL‐colesterol (LDL‐c), colesterol não-HDL (c‐NHDL), HDL‐colesterol (HDL‐c) e triglicérides (TG) em crianças e adolescentes saudáveis de Cuiabá. Método: Estudo transversal envolvendo 1.866 crianças e adolescentes saudáveis de creches e escolas municipais públicas de Cuiabá, aleatoriamente selecionadas. Os LD desejáveis dos lipídeos séricos foram definidos pelos critérios clássicos, isto é, níveis de CT, LDL‐c, c‐NHDL, TG abaixo do percentil 75, e de HDL‐c acima do percentil 10. Resultados: Os P75 para CT foram: 160 mg/dL para a faixa etária de 1 a < 3 anos, 170 mg/dL para ≥ 3 a < 9 anos e 176 mg/dL para ≥ 9 a < 13 anos. Para o c‐NHDL, de 122 mg/dL na faixa etária de 1 a < 13 anos. LDL‐c: 104 mg/dL na faixa etária de 1 a < 9 anos e 106 mg/dL de ≥ 9 a < 13 anos. TG: 127 mg/dL entre 1 a < 2 anos; 98 mg/dL de ≥ 2 a < 6 anos; e 92 mg/dL de ≥ 6 a < 13 anos. Quanto ao HDL‐c, o P10, foi de 24 mg/dL, 28 mg/dL, 32 mg/dL e 36 mg/dL, para as faixas etárias de 1 a < 2 anos, ≥ 2 a < 3 anos, ≥ 3 a < 4 anos e ≥ 4 a < 13 anos, respectivamente. Conclusão: Os LD dos níveis séricos de lipídeos definidos neste estudo diferem daqueles apresentados nas diretrizes brasileiras e americanas atuais, especialmente por fazer a diferenciação entre as idades. Utilizar tais LD em nossa prática clínica certamente contribuirá para melhorar a acurácia do diagnóstico de dislipidemia nesse grupo populacional. Keywords: Children, Adolescents, Reference intervals, Decision limits, Serum lipids, Palavras‐chave: Crianças, Adolescentes, Intervalos de referência, Limites de decisão, Lípides séricos